The Turn Toward Self-Responsibility in Current Societies: Differences, Challenges, and Perspectives. (January 2019) - Frericks, Patricia; Höppner, Julia
Current societies have undergone a many-faceted but also general turn toward self-responsibility. This is hardly contested, as shown by societal analyses of different kinds. Up to now though, the literature on self-responsibility has either focused on specific areas of society or hardly discussed the concept in sociological depth. In this special issue, we aim to do both. From a broad sociological and societal perspective the special issue analyses differences and communalities in the turn toward self-responsibility and highlights the challenges and perspectives it presents. The aim is a new discussion of the concept of self-responsibility that draws on actors' embeddedness in institutional environments and emphasizes the consequences of the development for individuals and societies.